DEVELOPMENT OF VIRTUAL LEARNING MODEL FLIPPED CLASSROOM - Mariyana, Rita; Zaman, Badru; Rudiyanto, Rudiyanto (Prodi PGPAUD, 2021)
This research introduces a new learning pedagogical approach, the Virtual Flipped Classroom (VFC). The VFC is an integration of two concepts: the Flipped Classroom and Virtual Teaching. This study aims to improve students’ learning abilities through the use of the flipped virtual classroom model. This research utilised a research and development, with a purposive sampling technique that studied active students in Early Childhood Teacher Education Program (henceforth-ECTE Program). Data from students’ final examination scores, questionnaires, were analyzed using quantitative and qualitative approach. The final products were a virtual model flipped classroom software along with its digital based classroom design.